Cancer multidisciplinary team meetings in practice: Results from a multi‐institutional quantitative survey and implications for policy change. Issue 1 (26th September 2017) - Rankin, Nicole M.; Lai, Michelle; Miller, Danielle; Beale, Philip; Spigelman, Allan; Prest, Gabrielle; Turley, Kim; Simes, John
Abstract: Aim: Multidisciplinary care is advocated as best practice in cancer care. Relatively little is documented about multidisciplinary team (MDT) meeting functioning, decision making and the use of evidence to support decision making in Australia. This descriptive study aimed to examine team functioning, the role of team meetings and evidence use in MDTs whose institutions are members of Sydney Catalyst Translational Cancer Research Centre. Methods: We designed a structured 40‐item survey instrument about topics that included meeting purpose, organization, resources and documentation; caseload estimates; use of evidence and quality assurance; patient involvement and supportive care needs; and open‐ended items about the MDTs strengths and weaknesses. Participants were invited to participate via email and the survey was administered online. Data were analyzed using descriptive and comparative statistics. Results: Thirty‐seven MDTs from seven hospitals participated (100% response) and represented common (70%) and rare tumor groups (30%). MDT meeting purpose was reported as treatment (100%) or diagnostic decision making (88%), or for education purposes (70%). Most MDTs based treatment decisions on group consensus (92%), adherence to clinical practice guidelines (57%) or other evidence‐based medicine sources (33%). The majority of MDTs discussed only a proportion of new patients at each meeting emphasizing the importance of educational aspects for other cases. Barriers exist in the availability of data to enable audit and reflection on evidence‐based practice. MDT strengths included collaboration and quality discussion about patients. Conclusions: MDT meetings focus on treatment decision making, with group consensus playing a significant role in translating research evidence from guidelines into clinical decision making. With a varying proportion of patients discussed in each MDT meeting, a wider audit of multidisciplinary care would enable more accurate assessments of whether treatment recommendations are in accordance with best‐practice evidence.